Religious Jurisdiction System: A Comparison In Brunei Darussalam And The Philippines - Syaputra, Ego; Asasriwarni, Asasriwarni; Zulfan, Zulfan (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2023)
Brunei Darussalam is a country that has an absolute monarchy style of government based on Islamic law with the Sultan serving as Head of State and Head of Government, concurrently serving as Prime Minister and Minister of Defense assisted by the Advisory Council of the Sultanate and several Ministers. Brunei or also called the Malay Islamic Kingdom (MIB) made Islam its national ideology. The method used in this study uses Library Research which is a data collection technique by examining various literature including journals, books, magazines, and other data sources, to link the results obtained from these various sources. Brunei's legal system is based on English common law, with an independent judiciary, judicial bodies, written common law statutes, and statutes passed by the Sultan. Courts have different jurisdictions, so the sentences imposed are different. The courts at that time were: (1) Resident Court, (2) First Instance Court, (3) Second Instance Court, and (4) Indigenous and Kathis Magistrates Court. Meanwhile, the Philippine Legal System is a blend of the Roman Civil Law System and the Anglo-American Common Law System. The Civil Law system operates in areas such as family relations, property, succession, contracts, and criminal law while the statutes and basic principles of Common Law are evident in areas such as constitutional law, procedure, corporate law, negotiating instruments, taxation, insurance, labor partner work, and banking law. Islamic law prevails and is recognized in parts of Mindanao with the establishment of Shari'ah courts. This research aims to find out how the religious justice system is in Brunei Darussalam and the Philippines. Brunei Darussalam adalah negara yang memiliki corak pemerintahan monarki absolut berdasar hukum Islam dengan Sultan yang menjabat sebagai Kepala Negara dan Kepala Pemerintahan, merangkap sebagai Perdana Menteri dan Menteri Pertahanan dengan dibantu oleh Dewan Penasehat Kesultanan dan beberapa Menteri. Brunei atau disebut juga Kerajaan Islam Melayu (MIB) benar-benar menjadikan Islam sebagai ideologi nasionalnya. Metode yang digunakan dalam penelitian ini mengunakan Studi Kepustakaan (Library Research) yang merupakan teknik pengumpulan data dengan melakukan penelaahan terhadap berbagai literatur-literatur pustaka diantaranya jurnal, buku, majalah,maupun sumber data lainnya, dengan tujuan menghubungkan hasil yang didapatkan dari berbagai sumber tersebut. Sistem hukum Brunei didasarkan pada hukum umum Inggris, dengan peradilan independen, badan penilaian dan undang- undang hukum umum tertulis, dan undang-undang yang disahkan oleh Sultan. Pengadilan mempunyai jurisdiksi yang berbeda, maka hukuman yang dijatuhkan pun berbeda-beda. Pengadilan-pengadilan pada masa itu: (1) Pengadilan Residen, (2) Pengadilan Hakim Tingkat Pertama, (3) Pengadilan Hakim Tingkat Kedua, serta (4) Pengadilan Hakim Pribumi dan Kathis. Sedangkan Sistem Hukum Filipina merupakan perpaduan dari Civil Law Roma dan Sistem Common Law Anglo-Amerika. Sistem Civil Law beroperasi di bidang hubungan keluarga, hak milik, suksesi, kontrak dan hukum pidana sementara statuta-statuta dan prinsip-prinsip dasar Common Law terlihat jelas dalam bidang seperti hukum konstitusional, prosedur, hukum korporasi, instrumen negosiasi, perpajakan, asuransi, tenaga kerja mitra, dan undang-undang perbankan. Hukum Islam berlaku dan diakui di beberapa bagian Mindanao dengan pembentukan pengadilan Shari'ah. Adapun penelitian ini bertujuan untuk mengtahui bagaimana sistem peradilan agama di Brunei Darussalam dan Filipina.